Brief Report: Understanding Preferences for HIV Care Among Patients Experiencing Homelessness or Unstable Housing. (1st December 2020) - Conte, Madellena; Eshun-Wilson, Ingrid; Geng, Elvin; Imbert, Elizabeth; Hickey, Matthew D.; Havlir, Diane; Gandhi, Monica; Clemenzi-Allen, Angelo
Abstract : Background: Homelessness and unstable housing (HUH) negatively impact care outcomes for people living with HIV (PLWH). To inform the design of a clinic program for PLWH experiencing HUH, we quantified patient preferences and trade-offs across multiple HIV-service domains using a discrete choice experiment (DCE). Methods: We sequentially sampled PLWH experiencing HUH presenting at an urban HIV clinic with ≥1 missed primary care visit and viremia in the last year to conduct a DCE. Participants chose between 2 hypothetical clinics varying across 5 service attributes: care team "get to know me as a person" versus not; receiving 10, 15, or 20 gift cards for clinic visits; drop-in versus scheduled visits; direct phone communication to care team versus front-desk staff; and staying 2 versus 20 blocks from the clinic. We estimated attribute relative utility (ie, preference) using mixed-effects logistic regression and calculated the monetary trade-off of preferred options. Results: Among 65 individuals interviewed, 61% were >40 years old, 45% White, 77% men, 25% heterosexual, 56% lived outdoors/emergency housing, and 44% in temporary housing. Strongest preferences were for patient-centered care team [β = 3.80; 95% confidence interval (CI): 2.57 to 5.02] and drop-in clinic appointments (β = 1.33; 95% CI: 0.85 to 1.80), with a willingness to trade 32.79 (95% CI: 14.75 to 50.81) and 11.45 (95% CI: 2.95 to 19.95) in gift cards/visit, respectively. Conclusions: In this DCE, PLWH experiencing HUH were willing to trade significant financial gain to have a personal relationship with and drop-in access to their care team rather than more resource-intensive services. These findings informed Ward 86's "POP-UP" program for PLWH-HUH and can inform "ending the HIV epidemic" efforts. Abstract : Supplemental Digital Content is Available in the Text.